SEMAVi DiNLERDE DÖRT BÜYÜK MELEK (CEBRAiL, MiKAiL, iSRAFiL, AZRAiL) - Serdar, Murat (Fırat University, 2008)
In the Islamic terminology Islam, Judaism and Christianity are named with "The Celestial Religions". In these religions the belief in angeis is a comman subject of the faith. There are many passages that build the angelic beliefs intheir sacred texts. Exist of the Angels and their natures, types, dasses and names are discussed in oftheir angelogies. The Major angels announced their names have been seen in every one of them. There are same similar creeds and knowledges about these angels among these religions. But alsa there are same different and contrary creeds among them. The Muslirns believe in that Gabriel, Michael, Saraphiel, Azrael are four rnajor angels. Qgbriel and Michael mentioned with these narnes in The Koran and Taralı and The Bibles. Azrael is not mentionedin the sacred books with this name. He is mentioned as "The Angel ofDeath" only. Alsa Seraphiel isn't mentionedin the sacred books. But he talked about himse!f in the jew's apokrative books and Prophet Muhammed's hadiths. The beliefs of religions about their works or duties and characteristics sametimes are smilar and samtimes are different. When we compare Islarn's angelic creeds with the other' s, we can say that Judaism and Christianity have got same opposite beliefs. Alsa we can say that there are same Marks demonstrate the Judaic effects on same of Muslim's angelic accepts. From the Kalamic perspective applying to Korarı is necessary for distinguishing between right and \vrong beliefs about the major angels.
The Four Major Angles in The Heavenly Religions (Gabriel, Michael, Saraphiel, Azrael)
Keywords: Religious Studies; Din Araştırmaları